Football and the representation of Basque identity in the contemporary age. (2nd January 2017) - Rojo-Labaien, Ekain
Abstract : Although the Basque Country has been historically divided between France and Spain, the long-standing collective identity of the Basque people endures. Football, a foreign sport that was regarded with suspicion in the early years of its introduction by the incipient Basque nationalist movement, became a pillar of differentiation with respect to Spain. It clearly surpassed the traditional Basque game of pelota as a collective affirmation. It did so firstly through a style of play forged in the imagined strength of the 'Basque race'. Later, especially in the late twentieth century, through the unusual autochthonous composition of the most important Basque clubs. This article sets out to capture the historical importance of football in the contemporary Basque Country as a complex patriotic vector and the difficulties that the absence of a Basque state entails for that objective. It also deals with the marked division in the sports field between the Spanish Basque Country and the French Basque Country, where Rugby became the sport that unified collectives.